Application of AI in medicine / Amirul Hisyam Tarmizi - Amirul Hisyam, Tarmizi (2000)
From the beginning of human civilization, mankind have been trying to fins solution on how to make life easier. They create, modify and adapt, as they would please their need. From the smallest things in our life to the biggest part of all technologies, has improved our life tremendously. Computer technology nowadays has an important role in education, communication, medicine, and many more. In the field of medicine, we have seen many support systems had been developed and use to help human in their daily lives. Application of AI in medicine was proposed in this reason in mind, as a hope that it can contribute toward the important of human life.